Feminism and Islam: A study of Maulvi Syed Mumtaz Ali’s thought in perspective of ‘Huqooq e Niswan’. - Dr. Shafique Anjum (Zaban-o-Adab, 2024)
Islam is a religion of nature and it has given mankind a complete code of life. However, the understanding, interpretation and application of Islamic concepts and rules have been different in different times and in different societies. The Islamic concept of woman is also a subject with a variety of interpretations. Traditionally and generally, the interpretation is well-known that Islam has made the female caste subordinate to the male and has given preference to the male. The same interpretation prevailed in Indian culture and the role of women in society was determined accordingly. Maulvi Syed Mumtaz Ali, a prominent nineteenth-century religious scholar, does not accept this prevailing notion of masculine virtue. In his view, masculine virtue is just a religion of illusion, ignorance and cultural traditions. Islam has nothing to do with it. The cruelty is that people misinterpreted Qur’anic verses and hadiths as evidence to prove this ignorant notion. To illustrate his point, he wrote a book in 1898 entitled Feminist Rights, which strongly criticized the notions of gender discrimination and cultural attitudes. He has argued in this book that all notions of masculine virtue are based on ignorance and prejudice. Islam has nothing to do with them. This article examines the feminist thought of Maulvi syed Mumtaz Ali in perspective of his book ‘Huqooq e Niswan’ and also discusses his scholarly abilities, biography and services.